2011
DOI: 10.1017/s0003598x00062141
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Coast Salish blankets: a tale of shaggy dogs?

Abstract: Identifying animals to species from relict proteins is a powerful new archaeological tool. Here the authors apply the method to answer questions relating to the Salish of west coast North America. Did they weave their blankets out of dog hair? The proteomic analysis shows that they did, interweaving it with goat, and that the woolly dog was increasingly superseded by sheep in the later nineteenth century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Hair and wool from sheep, cashmere and mohair goat, cow, yak, camel, alpaca, angora rabbit, and dog were obtained locally from fibre suppliers and farms. Llama, vicuna, guanaco, alpaca, Bactrian camel, yak, horse, deer and reindeer were sampled from the fibre collection at the Museum Conservation Institute and the mountain goat from the Smithsonian's National Museum of Natural History (NMNH) . Mouflon (origin Poland), and baleen were available at AgResearch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair and wool from sheep, cashmere and mohair goat, cow, yak, camel, alpaca, angora rabbit, and dog were obtained locally from fibre suppliers and farms. Llama, vicuna, guanaco, alpaca, Bactrian camel, yak, horse, deer and reindeer were sampled from the fibre collection at the Museum Conservation Institute and the mountain goat from the Smithsonian's National Museum of Natural History (NMNH) . Mouflon (origin Poland), and baleen were available at AgResearch.…”
Section: Methodsmentioning
confidence: 99%
“…Animal fibres have recently been identified using specific peptide markers from mass spectra acquired by MALDI‐TOF‐MS (matrix‐assisted laser desorption/ionisation time‐of‐flight mass spectrometry); peptides are obtained after trypsin digestion of proteins and identified by their mass‐to‐charge ratio ( m/z ). The technique was successful in identifying the different elements of the clothing of Oetzi, and to prove the existence of dog hair in Coast Salish blankets . In both cases, the textiles proved to be made of a wide range of species and the proteomics approach was particularly useful in characterising blends of fibres (dog/goat or sheep/goat) in the Coast Salish textiles.…”
mentioning
confidence: 99%
“…[49] Keratin-based species identification method Ancient proteins extracted and sequenced from fossil bones offer an extraordinary reservoir of genetic information that has recently become tractable through the application of mass spectrometric (MS) techniques. [24,27,49,50] Other sources of ancient proteins are dental pulps [51] or even contents of ceramics like amphorae. [52] Despite their potential use, hard keratins are an unexploited source of ancient proteins.…”
Section: Keratin Propertiesmentioning
confidence: 99%
“…In a slightly varied form the method was recently applied to species identification of domestic dog, sheep and goat in ancient Native Americans' woolen blankets. [50] …”
Section: Keratin Propertiesmentioning
confidence: 99%
“…PMF has been widely used on collagen from bone and soft tissues and specimens can generally be identified at the genus level but recent studies have shown that some markers were diagnostic to the species level in certain marine mammals (Kirby et al, 2013). PMFs of keratin in animal fibers have also been successfully used to identify ancient textiles and cloths (Solazzo et al, 2011;Hollemeyer et al, 2012).…”
Section: Species Identification Of Keratins Using Peptide Mass Fingermentioning
confidence: 99%